Refractive Status and Prevalence of Refractive Errors in Suburban School-age Children - Pi, Lian-Hong (Ivyspring International Publisher, 2010)
Objective: This study investigated the distribution pattern of refractive status and prevalence of refractive errors in school-age children in Western China to determine the possible environmental factors. Methods: A random sampling strategy in geographically defined clusters was used to identify children aged 6-15 years in Yongchuan, a socio-economically representative area in Western China. We carried out a door-to-door survey and actual eye examinations, including visual acuity measurements, stereopsis examination, anterior segment and eyeball movements, fundus examinations, and cycloplegic retinoscopy with 1% cyclopentolate. Results: A total of 3469 children living in 2552 households were selected, and 3070 were examined. The distributions of refractive status were positively-skewed for 6-8-year-olds, and negatively-skewed for 9-12 and 13-15-year-olds. The prevalence of hyperopia (≥+2.00 D spherical equivalent [SE]), myopia (≤-0.50 D SE), and astigmatism (≥1.00 diopter of cylinder [DC]) were 3.26%, 13.75%, and 3.75%, respectively. As children's ages increased, the prevalence rate of hyperopia decreased (P<0.001) and that of myopia increased significantly (P<0.001). Children in academically challenging schools had a higher risk of myopia (P<0.001) and astigmatism (≥1.00DC, P =0.04) than those in regular schools. Conclusion: The distribution of refractive status changes gradually from positively-skewed to negatively-skewed distributions as age increases, with 9-year-old being the critical age for the changes. Environmental factors and study intensity influence the occurrence and development of myopia.